Polyether alkanolamine dispersants for nanotube materials

Polyether alkanolamine dispersants effectively disperse carbon nanotubes in secondary battery electrodes, improving adhesion and reducing resistance, addressing the limitations of conventional dispersants in maintaining electrical and mechanical properties.

JP2025502268APending Publication Date: 2025-01-24NANOCOMP TECHNOLOGIES INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024542005
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-13
Filing Date
2023-01-13
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Carbon nanotubes are limited in applications due to low solubility and dispersibility, leading to agglomeration and deterioration of their electrical and mechanical properties when conventional dispersants are used, necessitating high costs and suboptimal performance.

Method used

A polyether alkanolamine dispersant is used to disperse carbon nanotubes in aqueous or organic solutions, enhancing their dispersibility without affecting electrical and mechanical characteristics, allowing for the formation of a better bond with current collectors in secondary battery electrodes.

Benefits of technology

The use of polyether alkanolamine dispersants results in improved adhesion to current collectors, reducing bulk resistance and enhancing the capacity of secondary battery electrodes, demonstrating lower resistance and better electrical conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502268000012
    Figure 2025502268000012
  • Figure 2025502268000013
    Figure 2025502268000013
  • Figure 2025502268000001
    Figure 2025502268000001
Patent Text Reader

Abstract

The present disclosure provides a nanotube dispersion comprising a dispersion medium, a polyether alkanolamine dispersant, and a carbon nanotube material, the nanotube dispersion being usable in a variety of applications, such as the manufacture of electrodes for secondary batteries.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Patent Application No. 63 / 299,163, filed Jan. 13, 2022. The aforementioned application is incorporated herein by reference.

[0002] STATEMENT REGARDING FEDERALLY SPONSORED RESEARCH OR DEVELOPMENT Not applicable.

[0003] Field The present disclosure generally relates to nanotube dispersions containing polyether alkanolamine dispersants, and to electrodes for secondary batteries comprising a current collector and a layer of the nanotube dispersion and an electrode active material disposed on the current collector, as well as secondary batteries comprising such electrodes. [Background technology]

[0004] Carbon nanotubes (hereinafter also referred to as "CNTs") have a cylindrical structure in which flat sheets of graphite (graphene sheets) are rolled up on themselves. Due to the peculiarities of their nanostructure, carbon nanotubes exhibit various properties. In particular, carbon nanotubes are superior to copper in terms of current density resistance, which is at least 1000 times higher than that of copper, thermal conductivity, which is about 10 times higher than that of copper, and tensile strength, which is about 20 times higher than that of steel. However, despite these useful properties, the use of carbon nanotubes in various applications is limited due to their low solubility and low dispersibility (i.e., carbon nanotubes experience strong van der Waals attractive forces between themselves, which leads to agglomerations rather than uniform dispersion).

[0005] Historically, polymers such as poly(styrenesulfonate) (PSS), poly(phenylacetylene) (PAA), poly(meta-phenylenevinylene) (PmPV), polypyrrole (PPy), poly(p-phenylenebenzobisoxazole) (PBO), and natural polymers have been used to wrap or coat carbon nanotubes to make them soluble in water or organic solvents. Carbon nanotubes have also been chemically modified by oxidation and fluorination or mixed using ultrasonication or high shear mixers to enhance the interaction of carbon nanotubes with the solvent and thus reduce their aggregation behavior. However, current dispersion techniques are not only expensive but can also lead to degradation of carbon nanotube properties, leading to reduced aspect ratios, introduction of defects, and the need for higher loadings to achieve desired performance.

[0006] That is, there is a need to provide a new dispersion technology that can effectively disperse carbon nanotubes in aqueous or organic solutions without affecting the electrical and mechanical properties of the carbon nanotubes, and that allows the dispersion to be subsequently used for various applications, such as the manufacture of electrodes for secondary batteries. Summary of the Invention

[0007] The present disclosure generally relates to a nanotube dispersion comprising a dispersion medium, a polyether alkanolamine dispersant, and a carbon nanotube material dispersed in the dispersion medium. In one embodiment, the carbon nanotube material has one or more of the following characteristics: (i) a diameter of about 1-100 nm, (ii) a length of about 0.1-10 mm, and (iii) a density of about 0.7-1.9 g / cm. 3 (iv) an aspect ratio of at least about 100,000; (v) a strain at break of about 1.8-7%; and (vi) a surface area of ​​about 100-300 m. 2 / g.

[0008] The present disclosure also provides a slurry for a secondary battery electrode comprising an electrode active material and the above-described nanotube dispersion.

[0009] The present disclosure also provides an electrode for a secondary battery comprising a current collector and a layer formed on the current collector, where the layer is formed from the secondary battery electrode slurry described above.

[0010] Finally, the present disclosure provides a secondary battery comprising a positive electrode, a negative electrode, an electrolyte, and a porous separator, in which the above-mentioned electrode for the secondary battery is used as at least one of the positive electrode and the negative electrode. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 illustrates a system for the direct collection of fully entangled networks of carbon nanotube material according to various embodiments. [Diagram 2] 1 is a graph showing the bulk resistivity of cathodes prepared from aqueous nanotube dispersions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present disclosure generally relates to nanotube dispersions containing a dispersion medium, a polyetheralkanolamine dispersant, and a nanotube material, such as a carbon nanotube material, dispersed in the dispersion medium. Surprisingly, it has been found that certain polyetheralkanolamines according to the present disclosure can be more effective than prior art dispersion techniques for dispersing carbon nanotube material in a dispersion medium containing water. Furthermore, due to this improved dispersibility, it is possible to replace organic solvents, such as 1-methyl-2-pyrrolidinone (a known toxic substance), commonly used in nanotube dispersions for the manufacture of electrodes for lithium ion batteries with a significant proportion of water. It has also been found that when a layer of an aqueous nanotube dispersion containing a polyetheralkanolamine dispersant is formed on a current collector, the adhesion of the nanotubes to the current collector is better, resulting in an electrode with lower bulk resistivity and improved capacity. This was unexpected and surprising. This is because electrodes made from aqueous nanotube dispersions that do not contain a polyetheralkanolamine dispersant are known to produce electrodes with poor adhesion to current collectors and low electrical conductivity.

[0013] The following terms shall have the following meanings:

[0014] The term "comprising" and its derivatives are not intended to exclude the presence of any additional elements, steps, or procedures, whether or not they are disclosed herein. In contrast, "consisting essentially of" is not intended to exclude the presence of any additional elements, steps, or procedures, whether or not they are disclosed herein. The term "essentially of," when it appears herein, excludes any other elements, steps, or procedures from any succeeding recitation unless they are essential to operability, and the term "consisting of," when used, excludes any element, step, or procedure not specifically delineated or listed. The term "or," unless otherwise stated, refers to the recited members individually as well as in any combination.

[0015] The articles "a" and "an" are used herein to refer to one or more of the grammatical object of the article. It is used to refer to more than one (i.e., at least one).

[0016] Phrases such as "in one embodiment," "according to one embodiment," and the like generally mean that the particular feature, structure, or characteristic that follows the phrase is included in at least one aspect of the disclosure, and may be included in more than one aspect of the disclosure. Importantly, such phrases do not necessarily refer to the same aspect.

[0017] Whenever "may," "can," "could," or "might" is used in this specification to describe that a certain element or feature is included or has a certain characteristic, it does not require that the particular element or feature be included or have the certain characteristic.

[0018] As used herein, the term "substantially free" refers to a composition or blend in which a particular compound or moiety is present in an amount that does not significantly affect the composition or blend. In some embodiments, "substantially free" may refer to a composition or blend in which a particular compound or moiety is present in an amount of less than 2% by weight, or less than 1% by weight, or less than 0.5% by weight, or less than 0.1% by weight, or less than 0.05% by weight, or even less than 0.01% by weight, based on the total weight of the composition or blend, or the absence of the amount of the particular compound or moiety present in the respective composition or blend.

[0019] The term "substantial proportion" refers to a percentage that is equal to or greater than 50%, 51%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 99%, or 100%, or a range between any two of these percentage values.

[0020] Values ​​expressed in range format should be interpreted in an open manner, not only to include the numerical values ​​specified as the limits of the range, but also to include all individual numerical values ​​or subranges subsumed within that range, as if each numerical value and subrange were specifically stated. For example, a range such as 1 to 6 should be considered to specifically disclose subranges such as 1 to 3, 2 to 4, 3 to 6, etc., as well as the individual numbers subsumed within that range, e.g., 1, 2, 3, 4, 5, and 6. This is true regardless of the breadth of the range.

[0021] The term "hydrocarbyl" refers to a univalent substituent containing only hydrogen and carbon atoms, which can be an aliphatic, aromatic, acyclic, or cyclic group and / or can be straight or branched chain. Examples include alkyl, cycloalkyl, alkenyl, alkadienyl, cycloalkenyl, cycloalkadienyl, aryl, and alkynyl groups.

[0022] It is contemplated that the term "dispersed" can include cases where the carbon nanotube material is present substantially throughout the entire dispersion medium, without being present in a substantially higher concentration anywhere in the dispersion medium. In addition, the term "dispersed" can also include cases where the carbon nanotube material is present in localized areas of the dispersion medium.

[0023] According to one embodiment, the nanotube dispersion can include a polyetheralkanolamine dispersant. Polyetheralkanolamine dispersants useful in the present disclosure are described in US 2008 / 0119613, the contents of which are incorporated herein by reference.

[0024] That is, in one embodiment, the polyether alkanolamine dispersant has the formula: A mixture comprising a compound having the structure of formula (1) and a compound having the structure of formula (2): [ka] [ka] where each R1 is C1-C 100 and each R2 is an alkoxylated hydrocarbyl group having the structure [ka] In the formula, R3 is C1-C 24are hydrocarbyl groups, where X1, X2, X3, X4, X5, and X6, at each occurrence, are independently selected from the group consisting of hydrogen, methyl, and ethyl, subject to the proviso that at least one of the two X groups attached to the same alkoxy unit is hydrogen; p, q, and r can each independently be an integer from 0 to about 100, subject to the proviso that at least one of p, q, and r is not 0; and each n is any integer from 1 to about 50. In one embodiment, when the hydrocarbyl group is aromatic, each n is any integer from 1 to about 10. In another embodiment, when the hydrocarbyl group is aliphatic, each n is any integer from 1 to about 50.

[0025] Polyether alkanolamine dispersants can be obtained by the reaction of monofunctional amine-terminated polyethers with polyol glycidyl ethers. The monofunctional amine-terminated polyether reactants and the polyol glycidyl ether reactants can each comprise a mixture of monofunctional amine-terminated polyethers and polyol glycidyl ethers, respectively. In some embodiments, the monofunctional amine-terminated polyether is present in an amount sufficient to ensure that the total number of reactive hydrogen atoms on the nitrogen atoms of the amine is at least stoichiometrically equal to the amount of epoxide groups present in the polyol glycidyl ether. This reaction can generally be represented as follows: [ka] and [ka] In the above reaction, each R1 is any C1-C 100 each n can be any integer from 1 to about 50; each R can be any hydrocarbyl group that includes as part of its molecular structure a moiety having at least two alkoxy groups linked together, i.e., the R group can be a hydrocarbyl group having the structure: [ka] In the formula, R3 is C1-C 24 are hydrocarbyl groups; X1, X2, X3, X4, X5, and X6, at each occurrence, are independently selected from the group consisting of hydrogen, methyl, and ethyl, subject to the proviso that at least one of the two X groups attached to the same alkoxy unit is hydrogen; p, q, and r can each independently be an integer from 0 to about 100, subject to the proviso that at least one of p, q, and r is not 0; and s is 0 or 1.

[0026] That is, a monofunctional amine-terminated polyether can be represented by a compound having the structure [ka] wherein R3, X1, X2, X3, X4, X5, X6, p, q, r, and s are defined as above. Thus, the structures include, but are not limited to, compounds having both random and block polymers, as well as copolymers containing any one or more of the following, alone or mixed with each other in any proportion: ethylene oxide ("EO"), propylene oxide ("PO"), and butylene oxide ("BO"). According to one embodiment, the monofunctional amine-terminated polyether has a molecular weight of about 100 to about 12,000 daltons, or about 250 to about 3500 daltons, or about 1000 to about 3000 daltons, or about 1500 to about 2000 daltons. In embodiments where a mixture of monofunctional amine-terminated polyethers is used to prepare the polyether alkanolamines provided herein, the molecular weight will be the average molecular weight of all amines present.

[0027] Specific examples of monofunctional amine-terminated polyethers that can be used include JEFFAMINE® M-1000 amine (a polyethylene glycol-based methyl-capped amine having a molecular weight of 1000), JEFFAMINE® M-600 amine (a polypropylene glycol-based methyl-capped amine having a molecular weight of 600), JEFFAMINE® M-2070 amine (a polyethylene glycol-based methyl-capped amine having a molecular weight of 2070), JEFFAMINE® M-2005 amine (a polypropylene glycol-based methyl-capped amine having a molecular weight of 2005), SURFONAMINE® B-60 amine (a 600 molecular weight methyl-capped amine), and SURFONAMINE® B-70 amine (a 600 molecular weight methyl-capped amine). PO / EO ratio of 9 / 1), SURFONAMINE® EL-100 amine (a methyl-capped amine having a molecular weight of 1000 and a PO / EO ratio of 3 / 19), SURFONAMINE® B-200 amine (a methyl-capped amine having a molecular weight of 2000 and a PO / EO ratio of 29 / 6), SURFONAMINE® L-207 amine (a methyl-capped amine having a molecular weight of 2000 and a PO / EO ratio of 10 / 31), SURFONAMINE® L-300 amine (a methyl-capped amine having a molecular weight of 3000 and a PO / EO ratio of 8 / 58), SURFONAMINE® B-30 amine (a methyl-capped amine having a molecular weight of 325 and a PO / EO ratio of 3 / 19), SURFONAMINE® EL-200 amine (a methyl-capped amine having a molecular weight of 1000 and a PO / EO ratio of 3 / 19), SURFONAMINE® B-200 amine (a methyl-capped amine having a molecular weight of 2000 and a PO / EO ratio of 29 / 6), SURFONAMINE® L-207 amine (a methyl-capped amine having a molecular weight of 2000 and a PO / EO ratio of 10 / 31), SURFONAMINE® L-300 amine (a methyl-capped amine having a molecular weight of 3000 and a PO / EO ratio of 8 / 58), SURFONAMINE® B-30 amine (a methyl-capped amine having a molecular weight of 325 and a PO / EO ratio of 3 / 19), 13 and SURFONAMINE® B-100 amine (a nonylphenyl-capped amine with a molecular weight of 1004 and 13.5 parts PO).

[0028] In one particular embodiment, the monofunctional amine-terminated polyether is a compound having the structure: [ka] wherein R1 and R2 are each independently selected from the group consisting of hydrogen and a C1-C4 hydrocarbyl group; R3 is selected from the group consisting of hydrogen, methyl, methoxy, ethoxy, and hydroxy; and n is any integer ranging from about 5 to 100.

[0029] Polyol glycidyl ethers can be obtained from the reaction of a compound having at least two free alcoholic and / or phenolic hydroxyl groups with epichlorohydrin or β-methylepichlorohydrin under alkaline conditions or in the presence of an acid catalyst followed by alkaline treatment.

[0030] Glycidyl ethers of this kind are, for example, based on acyclic alcohols, such as ethylene glycol, diethylene glycol or higher poly(oxyethylene) glycols, These can be based on propane-1,2-diol or poly(oxypropylene) glycol, propane-1,3-diol, butane-1,4-diol, poly(oxytetramethylene) glycol, pentane-1,5-diol, hexane-1,6-diol, hexane-2,4,6-triol, glycerol, 1,1,1-trimethylolpropane, pentaerythritol or sorbitol. Further glycidyl ethers of this type can be based on cycloaliphatic alcohols, such as 1,4-cyclohexanedimethanol, bis(4-hydroxycyclohexyl)methane or 2,2-bis(4-hydroxycyclohexyl)propane, or alcohols with aromatic groups and / or further functional groups, such as N,N-bis(2-hydroxyethyl)aniline or p,p'-bis(2-hydroxyethylamino)-diphenylmethane.

[0031] The glycidyl ethers can be based on mononuclear phenols such as p-tert-butylphenol, resorcinol, or hydroquinone, or polynuclear phenols such as bis(4-hydroxyphenyl)methane, 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)sulfone, 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane, or 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane.

[0032] Further hydroxy compounds suitable for the preparation of glycidyl ethers are novolaks which can be obtained by condensation of aldehydes, such as formaldehyde, acetaldehyde, chloral or furfuraldehyde, with phenols or bisphenols, which are unsubstituted or contain chlorine atoms or C1-C 9 Substituted with an alkyl group, for example phenol, 4-chlorophenol, 2-methylphenol, or 4-tert-butylphenol.

[0033] In one embodiment, representative polyol glycidyl ethers of particular interest are those based on monocyclic phenols such as resorcinol or hydroquinone, those based on polycyclic phenols such as bis(4-hydroxyphenyl)methane (bisphenol F), 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), bis(4-hydroxyphenyl)sulfone (bisphenol S), alkoxylated bisphenol A, F, or S, triol-extended bisphenol A, F, or S, brominated bisphenol A, F, or S, hydrogenated bisphenol A, F, or S, glycidyl ethers of phenol and phenols with pendant groups or chains, those based on condensates of phenol or cresol with formaldehyde obtained under acidic conditions such as phenol novolacs and cresol novolacs, or those based on siloxane diglycidyls.

[0034] The monofunctional amine-terminated polyether reactant and the polyol glycidyl ether reactant are present in amounts such that the amine groups of the polyether can be consumed by reacting with essentially all of the epoxide functionality of the glycidyl ether. That is, during the reaction, the amount of monofunctional amine-terminated polyether is stoichiometrically equal to or greater than the amount of epoxide of the polyol glycidyl ether. The resulting product is free of substantially any unreacted epoxide functionality left after the reaction.

[0035] Depending on the amount of initiator employed, it is possible to form either secondary or tertiary amines in the final product. Thus, it is possible to form a product containing repeat units in which a monofunctional amine-terminated polyether has reacted with two epoxide groups to form a tertiary amine. This product can be represented by the representative formula: RNHCH2CH(OH)CH2-[-OAO-CH2CH(OH)CH2NRCH2CH(OH)CH2-O-] x -AO-CH2CH(OH)CH2-NHR where R represents the capped polyether portion of a monofunctional amine-terminated polyether, A represents the hydrocarbyl radical of a polyol glycidyl ether, e.g., the hydrocarbon portion of bisphenol A, and x can vary from 0 (when no tertiary amine is present) to about 100.

[0036] In one embodiment, the nanotube dispersion comprises at least about 0.01 wt.% polyetheralkanolamine dispersant based on the total weight of the nanotube dispersion. In yet other embodiments, the nanotube dispersion comprises at least about 0.05 wt.%, or at least about 0.1 wt.%, or at least about 0.25 wt.%, or at least about 0.5 wt.%, or at least about 0.75 wt.%, or at least about 1 wt.% polyetheralkanolamine dispersant based on the total weight of the nanotube dispersion.

[0037] In another embodiment, the nanotube dispersion comprises less than about 20% by weight of polyetheralkanolamine dispersant based on the total weight of the nanotube dispersion. In yet other embodiments, the nanotube dispersion comprises less than about 15% by weight, or less than about 10% by weight, or less than about 7.5% by weight, or less than about 5% by weight, or less than about 4% by weight, or less than about 3% by weight of polyetheralkanolamine dispersant based on the total weight of the nanotube dispersion.

[0038] In yet another embodiment, the nanotube dispersion comprises from about 0.01% to about 15% by weight of polyetheralkanolamine dispersant based on the total weight of the nanotube dispersion, hi yet another embodiment, the nanotube dispersion comprises from about 0.05% to about 7.5% by weight, or from about 0.1% to about 5% by weight, or from about 0.25% to about 2.5% by weight, or from about 0.5% to about 1.5% by weight of polyetheralkanolamine dispersant based on the total weight of the nanotube dispersion.

[0039] The nanotube dispersion further comprises a dispersion medium, which can be aqueous or organic. In one embodiment, the dispersion medium may be water, chloroform, chlorobenzene, acetic acid, acetone, acetonitrile, aniline, benzene, benzonitrile, benzyl alcohol, bromobenzene, bromoform, 1-butanol, 2-butanol, carbon disulfide, carbon tetrachloride, cyclohexane, cyclohexanol, decalin, dibromethane, diethylene glycol, diethylene glycol ether, diethyl ether, diglyme, dimethoxymethane, dihydrolevoglucosanone (silene), N,N-dimethylformamide, ethanol, ethylamine, ethylbenzene, ethylene glycol ether, ethylene glycol, ethylene glycol acetate, propylene glycol, propylene glycol acetate, ethylene oxide, formaldehyde, formic acid, glycerol, heptane, hexane, iodobenzene, 2-methyloxolane, mesitylene, methanol, methoxybenzene, methylamine, methylene bromide, methylene chloride, methylpyridine, morpholine, naphthalene, nitrobenzene, nitromethanone, methylpyridine ... , octane, pentane, pentyl alcohol, phenol, 1-propanol, 2-propanol, terpineol, texanol, carbitol, carbitol acetate, butyl carbitol acetate, dibasic esters, propylene carbonate, pyridine, pyrrole, pyrrolidine, quinoline, 1,1,2,2-tetrachloroethane, tetrachloroethylene, tetrahydrofuran, tetrahydropyran, tetralin, tetramethylethylenediamine, thiophene, toluene, 1,2,4-trichlorobenzene benzene, 1,1,1-trichloroethane, 1,1,2-trichloroethane, trichloroethylene, triethylamine, triethylene glycol dimethyl ether, 1,3,5-trimethylbenzene, 3-methyl-2-oxazolidinone, N,N'-dimethylethylene urea, m-xylene, o-xylene, p-xylene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2-dichloroethane, N-methyl-2-pyrrolidone, methyl ethyl ketone, dioxane, dimethylsulfate In one embodiment, the dispersion medium is substantially free of N-methyl-2-pyrrolidone. In another embodiment, the dispersion medium includes at least one of 3-methyl-2-oxazolidinone and N,N'-dimethylethyleneurea.

[0040] In another embodiment, the dispersion medium is an aqueous dispersion medium and contains a substantial proportion of water to impart at least some of the polarity and solubility characteristics of water to the medium. Suitably, the aqueous dispersion medium contains at least 50%, at least 60%, at least 75%, at least 90%, at least 95%, at least 98%, or at least 99% (e.g., essentially 100% in some embodiments) water by weight based on the total weight of the aqueous dispersion medium.

[0041] The dispersion also contains nanotube material dispersed in the dispersion medium.

[0042] According to one embodiment, the nanotube material comprises carbon nanotubes having the following specific characteristics: (i) a diameter of about 1-100 nm, or about 5-100 nm, or about 12-90 nm, or about 15-80 nm, or about 17-60 nm, or about 20-50 nm, or about 25-30 nm; (ii) a length of about 0.01-10 mm, or about 0.1-10 mm, or about 0.2-9 mm, or about 0.3-8 mm, or about 0.44-7 mm, or about 5 mm-6 mm, or about 1-6 mm, or about 5-6 mm, or 1-10 mm, or greater than 1 mm; (iii) a density of about 0.3-1.9 g / cm. 3 , or about 0.35 to 1.8 g / cm 3 , or about 0.5 to 1.7 g / cm 3 , or about 0.1 to 1 g / cm 3 , or about 0.3 to 1.1 g / cm 3(iv) an aspect ratio of at least about 10,000, or at least about 100,000, or at least about 250,000, or at least about 350,000, or at least about 500,000, or at least about 600,000; (v) a breaking strain of about 1.8-7%, or about 2-6.5%, or about 3-5%; (vi) and a surface area of ​​about 100-300 m 2 / g, or about 125 to 275 m 2 / g, or about 150-250m 2 / g, or about 175-225m 2 In further embodiments, the carbon nanotubes may be characterized in addition to the above characteristics by a tensile strength of about 0.2-3.2 GPa, or about 0.3-3 GPa, or about 0.3-2.8 GPa, and / or a specific strength of about 1800-2900 kN·M / kg, or about 2000-2700 kN·M / kg, or about 2200-2600 kN·M / kg.

[0043] In one embodiment, the carbon nanotubes are at least partially entangled with each other.

[0044] Currently, there are several processes and variations thereof for growing nanotubes and forming them into yarn, sheet, or cable structures for use as carbon nanotube material feedstocks for nanotube dispersions, including: (1) chemical vapor deposition (CVD), a common process that can occur at or near ambient pressure or at elevated pressures and at temperatures above about 400° C., (2) arc discharge, a high temperature process that can produce tubes with a high degree of perfection, and (3) laser ablation.

[0045] In some embodiments, a CVD process or similar gas phase pyrolysis procedure known in the industry can be used to produce suitable nanotube materials. The growth temperature of the CVD process can be in the relatively low range, for example, from about 400° C. to about 1350° C. Carbon nanotubes, either single-walled carbon nanotubes (SWNTs) or multi-walled carbon nanotubes (MWNTs), can be grown, in some embodiments, by contacting nanoscale catalyst particles in the presence of a carbon-containing gas (i.e., a gaseous carbon source) as a reagent. In particular, nanoscale catalytic particles can be introduced either by adding existing particles to the carbon-containing gas as a reagent, by in situ synthesis of particles from metal-organic precursors, or even by non-metallic catalysts. Although both SWNTs and MWNTs can be grown, in certain cases SWNTs may be chosen due to their relatively high growth rate and tendency to form rope-like structures, which may provide advantages in handling, thermal conductivity, electrical properties, and strength.

[0046] Carbon nanotubes utilized in this disclosure may be described as bare, unmodified, unrefined, or refined, with or without solubility in a given organic or aqueous dispersion medium prior to the addition of the polyetheralkanolamine dispersant. The terms "bare" and / or "unmodified" and / or "unrefined" describe carbon nanotubes that have undergone little or no processing since being chemically synthesized. These types of carbon nanotubes are primarily, but not limited to, materials that can be obtained directly from a synthesis process. The term "purified" carbon nanotubes is defined as carbon nanotubes that have been primarily chemically and / or thermally and / or physically treated to impart improved properties to the carbon nanotubes. Examples of such treatments include, but are not limited to, heat and acid treatments to remove catalysts or amorphous carbon, and thermal annealing to remove catalysts and / or reduce the number of carbon defect sites. Additionally, to aid in the dispersion and processing of the carbon nanotubes, the carbon nanotubes may be subjected to a media mill to break down carbon nanotube aggregates. A variety of methods and approaches to purifying carbon nanotubes exist in the literature, and material prepared by any such technique can be utilized in the present disclosure.

[0047] It should be noted that although reference is made throughout this application to nanotubes synthesized from carbon, other compound(s) such as boron nitride, MoS2, or combinations thereof may be used to synthesize nanotubes in connection with the present disclosure. Furthermore, other methods, such as plasma CVD, may also be used to produce the nanotubes of the present disclosure.

[0048] In general, the carbon nanotube material can be any nanotube material, such as, for example, carbon nanotube sheets, carbon nanotube strips, carbon nanotube tapes, bulk collected carbon nanotubes, carbon nanotube yarns, any other suitable carbon nanotube material containing entangled carbon nanotubes, or combinations thereof.

[0049] In some embodiments, the carbon nanotube material can be produced by a floating catalyst chemical vapor deposition (FC-CVD) method as described in U.S. Patent No. 8,999,285, the contents of which are incorporated herein in their entirety. The FC-CVD method of producing carbon nanotubes can result in very long nanotubes (>100 microns) that become fully entangled while still in the gas phase as they are produced. As the carbon nanotube material emerges from the hot zone of the furnace, the nanotubes entangle, bundle, and in any case coalesce into an extended network of interconnected branched bundles that cannot be obtained by other carbon nanotube production processes.

[0050] 1, carbon nanotube material can be collected from a FV-CVD reactor by a collection system 2000. In some embodiments, the system 2000 can be coupled to a synthesis chamber 2001. The synthesis chamber 2001 generally includes an inlet end 2001a through which reactant gases can be supplied, a hot zone 2002 in which synthesis of extended length nanotubes can occur, as well as a reaction product, the so-called extended length nanotube. and an outlet end 2001b through which the extended length of nanotubes and spent gases can exit and be collected. In some embodiments, the synthesis chamber 2001 can include a tube 2003 that extends through the hot zone 2002. Although generally illustrated in FIG. 1, it will be appreciated that other configurations can be employed in the design of the synthesis chamber 2001.

[0051] In some embodiments, system 2000 comprises an enclosure 2005, as shown in Figure 1, that is substantially airtight to minimize the release of potentially harmful airborne particles from the interior of synthesis chamber 2001 into the environment and to prevent oxygen from entering system 2000 and reaching synthesis chamber 2001. In particular, the presence of oxygen within synthesis chamber 2001 can affect the integrity and impair the production of nanotubes.

[0052] The system 2000 may also include an inlet 2005a of the housing 2005 for engaging the outlet end 2001b of the synthesis chamber 2001 in a substantially airtight manner. In some embodiments, as the carbon nanotubes exit the synthesis chamber 2001, the nanotubes tangle, bundle, and otherwise coalesce into an extended network of interconnected branched bundles. In some embodiments, such extended networks tend to form hollow carbon nanotube "socks" that resemble the shape of a windsock inflated by the wind. That is, the carbon nanotubes may be collected from the synthesis chamber 2001 in the housing 2005 by pulling the carbon nanotube sock 2007 onto a rotating mesh substrate 2009 (e.g., by drawing a vacuum on the back of the mesh substrate 2009) and removing the carbon nanotubes from the mesh substrate 2009 with a tool 2011, as shown in FIG. 1.

[0053] Although described above with respect to collection system 2000 having a mesh substrate 2009 collection mechanism, it will be apparent in light of this disclosure that in some embodiments, any technique for collecting and removing carbon nanotubes from the FC-CVD environment without destroying the substantial entanglement of the carbon nanotubes can be used in accordance with various embodiments. For example, in some embodiments, collection of carbon nanotubes produced by FC-CVD can be accomplished by forming carbon nanotube yarns or tows (e.g., by twisting the collected carbon nanotubes together) and / or forming carbon nanotube sheets as described in U.S. Patent Nos. 7,993,620 and 8,722,171, the contents of each of which are incorporated herein in their entirety.

[0054] In some embodiments, the carbon nanotubes may initially contain iron or other inclusions. In other embodiments, such inclusions are undesirable and may be removed, preferably prior to use. For example, in some embodiments, iron inclusions may be eliminated from the carbon nanotubes by heating the carbon nanotubes to high temperatures (e.g., about 1800° C.) in an inert or reducing atmosphere. At such temperatures, the iron may evaporate out of the carbon nanotubes and resolidify on a cooler surface. In some embodiments, such removal of inclusions may be accomplished, for example, in a CVD reactor, such as the FV-CVD reactor described above, or any CVD reactor, such as those described in U.S. Pat. Nos. 8,999,285 and 7,993,620, the contents of each of which are incorporated herein in their entirety.

[0055] In some embodiments, inclusions, such as iron inclusions, can be removed by heating the carbon nanotube material to about 500° C. in air and then treating with an acid. It can be heated for 2 hours and then treated with muriatic acid to remove the iron content.

[0056] In some embodiments, the carbon nanotubes are non-functional. In other embodiments, the carbon nanotubes in the nanotube material can be physically modified (e.g., sonicated or coated) or chemically modified (e.g., with acids, solvents, polymers, or oxidizing agents). Such modifications can involve the ends, sidewalls, or both of the carbon nanotubes. Physical and chemical modifications can include, but are not limited to, covalent bonding, ionic bonding, chemisorption, intercalation, surfactant interactions, polymer wrapping, scission, solvation, and combinations thereof that result in the addition of functional groups to the carbon nanotubes, such as, but not limited to, -COOH, -PO4, -PO5, -PO6, -PO7, -PO8, -PO9, -PO10, -PO4, -PO5, -PO6, -PO7, -PO8, -PO9, -PO10, -PO11, -PO12, -PO13, -PO14, -PO15, -PO16, -PO17, -PO18, -PO19, -PO20, -PO21, -PO22, -PO23, -PO24, -PO25, -PO30, -PO40, -PO45, -PO46, -PO47, -PO48, -PO49 ... - , -SO3 - , -SO3H, -SH, -NH2, tertiary amines, quaternized amines, -CHO, and / or -OH. In one embodiment, the chemical modification can include, for example, modification with polysilazanes, polyureasilazanes, conductive polymers, polyamines, polythiophenes, infiltration with polyamides, chemical modification to introduce carboxylate or amine functional groups, any modification suitable for improving ionic conductivity, or combinations thereof. In another particular embodiment, the functionalized carbon nanotubes include organic and / or inorganic compounds attached to their surface, with non-limiting examples of such organic compounds including at least one chemical group selected from the following: carboxyl, amine, polyamide, polyamphiphile, diazonium salt, pyrenyl, silane, and combinations thereof, and non-limiting examples of such inorganic compounds including at least one fluorine compound of boron, titanium, niobium, tungsten, and combinations thereof. The inorganic and organic compounds can also include halogen atoms or halogenated compounds. In some embodiments, the carbon nanotubes are functionalized at about 5%-100%, or about 10%-90%, or about 25%-75%, or about 50%-75%, or about 50%-100% of the sites available for functionalization.

[0057] According to one embodiment, the nanotube dispersion comprises at least about 0.001 wt.% carbon nanotube material based on the total weight of the nanotube dispersion. In yet other embodiments, the nanotube dispersion comprises at least about 0.005 wt.%, or at least about 0.01 wt.%, or at least about 0.1 wt.%, or at least about 0.25 wt.%, or at least about 0.5 wt.%, or at least about 0.75 wt.%, or at least about 1 wt.% carbon nanotube material based on the total weight of the nanotube dispersion.

[0058] According to another embodiment, the nanotube dispersion comprises less than about 20% by weight of carbon nanotube material based on the total weight of the nanotube dispersion. In yet other embodiments, the nanotube dispersion comprises less than about 10% by weight, or less than about 7.5% by weight, or less than about 5% by weight, or less than about 2.5% by weight of carbon nanotube material based on the total weight of the nanotube dispersion.

[0059] In yet another embodiment, the nanotube dispersion comprises from about 0.001% to about 20% by weight of carbon nanotube material based on the total weight of the nanotube dispersion, hi yet another embodiment, the nanotube dispersion comprises from about 0.01% to about 7.5% by weight, or from about 0.1% to about 5% by weight, or from about 0.25% to about 2.5% by weight, or from about 0.5% to about 1% by weight of carbon nanotube material based on the total weight of the nanotube dispersion.

[0060] The nanotube dispersion also contains a dispersion additive. Examples of dispersing additives include polyvinylpyridine (e.g., poly(4-vinylpyridine) or poly(2-vinylpyridine)), polystyrene (PS), poly(4-vinylpyridine-co-styrene), poly(styrenesulfonate) (PSS), lignosulfonic acid, lignosulfonates, poly(phenylacetylene) (PPA), poly(meta-phenylenevinylene) (PmPV), polypyrrole (PPy), poly(p-phenylenebenzobisoxazole) (PBO), naturally occurring polymers, anionic aliphatic surfactants, poly(vinyl alcohol), polyvinyl alcohol, ... ) (PVA), polyoxyethylene surfactants, poly(vinylidene fluoride) (PVDF), cellulose derivatives (generally and particularly those in which some hydroxyl groups of glucose units are substituted with methyl or ethyl or higher groups, e.g., methylcellulose (MC) or ethylcellulose (EC), cellulose derivatives in which hydrogen atoms of some hydroxyl groups of glucose units are substituted with hydroxymethyl, hydroxyethyl, hydroxypropyl, or higher groups, e.g., hydroxymethylcellulose (HM Examples of the cellulose derivatives include, but are not limited to, cellulose derivatives in which hydrogen atoms of some hydroxyl groups of glucose units are substituted with carboxymethyl, carboxyethyl, or higher groups, such as carboxymethyl cellulose (CMC) or carboxyethyl cellulose (CEC) or salts of CMC (including sodium carboxymethyl cellulose (Na-CMC) and lithium CMC (Li-CMC)), cellulose derivatives in which hydrogen atoms of some hydroxyl groups of glucose units are substituted with alkyl groups and hydroxyalkyl groups, such as hydroxyethyl methyl cellulose (HEMC) or hydroxypropyl methyl cellulose (HPMC), mixtures of different cellulose derivatives, polyacrylic acid (PAA), polyvinyl chloride (PVC), polysaccharides, styrene-butadiene rubber (SBR), polyamides, polyimides, block copolymers (e.g., acrylic block copolymers, ethylene oxide-propylene oxide copolymers), and mixtures thereof.

[0061] According to one embodiment, the nanotube dispersion comprises at least about 0.001 wt.% of one or more dispersion additives, based on the total weight of the nanotube dispersion. In yet other embodiments, the nanotube dispersion comprises at least about 0.05 wt.%, or at least about 0.1 wt.%, or at least about 0.5 wt.%, or at least about 1 wt.%, or at least about 2 wt.%, or at least about 3.5 wt.%, or at least about 4 wt.% of one or more dispersion additives, based on the total weight of the nanotube dispersion.

[0062] In another embodiment, the nanotube dispersion comprises less than about 20% by weight of one or more dispersion additives, based on the total weight of the nanotube dispersion. In yet other embodiments, the nanotube dispersion comprises less than about 15% by weight, or less than about 10% by weight, or less than about 8% by weight, or less than about 7% by weight, or less than about 6% by weight, or less than about 5% by weight, or less than about 2.5% by weight of one or more dispersion additives, based on the total weight of the nanotube dispersion.

[0063] In yet another embodiment, the nanotube dispersion comprises from about 0.001% to about 15% by weight of one or more dispersion additives, based on the total weight of the nanotube dispersion. In yet other embodiments, the nanotube dispersion comprises from about 0.5% to about 10% by weight, or from about 1% to about 7% by weight of one or more dispersion additives, based on the total weight of the nanotube dispersion.

[0064] The nanotube dispersion can also optionally include another conductive material, which can be a conductive material other than carbon nanotube material, examples of which include: conductive carbon materials, such as graphite, carbon black (e.g., acetylene black and furnace black), carbon nanohorns, vapor-grown carbon fibers, milled carbon fibers obtained by pyrolysis of polymer fibers followed by pulverization, single- or multi-walled carbon fibers, and the like. carbon nonwoven sheets obtained through pyrolysis of nonwoven fabrics made of polymer fibers, fibers of various metals and metal foils, and any combination thereof. In one embodiment, the mass ratio of the carbon nanotube material to the conductive material other than the carbon nanotube material is 1:10 to 10:1 or 1:3 to 3:1. The conductive material can also be added as a separate dispersion or as a powder in the preparation of the following electrode slurry.

[0065] In some embodiments, the total solids concentration in the nanotube dispersion can be 1% or more, or 2% or more, or even 3% or more, and 20% or less, or 15% or less, or even 12% or less by weight.

[0066] The nanotube dispersion can be prepared by dispersing and mixing the above-mentioned components. The mixing method is not particularly limited, and can be carried out, for example, by using a known mixer, such as a homogenizer, a Henschel mixer, a Banbury mixer, a ribbon mixer, a V-type mixer, a planetary centrifugal mixer, a bead mill, a ball mill, a sand mill, a pigment disperser, a grinder, an ultrasonic disperser, a three-roll mill, a lower stator mixer, or a Filmix mixer.

[0067] The nanotube dispersions of the present disclosure exhibit improved dispersibility of carbon nanotube material within the nanotube dispersion and can be used in connection with a variety of systems, such as secondary battery systems, water-based epoxy systems, printing ink systems, or polymer systems.

[0068] That is, in one embodiment, the nanotube dispersion, in any of its various embodiments, is useful for forming nanotube films on a substrate to form articles having a variety of desired electrical, mechanical, and / or thermal properties.

[0069] The nanotube film can be formed by applying the nanotube dispersion to a substrate surface by contacting the substrate with the dispersion medium comprising the polyether alkanolamine dispersant and the carbon nanotube material by any suitable means, such as by painting, spraying, coating, and / or dipping. At least a portion of the dispersion medium is then removed to form a nanotube film comprising the carbon nanotube material therein. Removal of the dispersion medium can be accomplished by any suitable means, such as by actively drying / heating the dispersion medium on the substrate or simply allowing the dispersion medium to evaporate over time. While in some embodiments it is not necessary to remove all of the dispersion medium to form a film, in practice all or a significant portion of the dispersion medium is removed to form a final nanotube film having the desired electrical and strength properties. In some embodiments, the nanotube film formation process can be repeated to fabricate a thicker film. For example, the substrate to which the nanotube dispersion is to be applied has a previously formed nanotube film of the same or a different composition, resulting in a multi-layer film.

[0070] The nanotube film can have any desired thickness, which will generally be based on the selection of nanotube dispersion component concentrations and the number of film forming steps performed in producing the nanotube film. Specifically, the nanotube film can generally have a thickness ranging from about 0.02 μm to about 500 μm, e.g., at least about 0.02 μm, at least about 0.2 μm, at least about 1 μm, at least about 2 μm, at least about 5 μm, at least about 10 μm, or at least about 20 μm, and / or up to about 10 μm, up to about 20 μm, up to about 50 μm, up to about 100 μm, up to about 200 μm, up to about 300 μm, or up to about 500 μm.

[0071] The specific substrate on which the nanotube dispersion is applied (and ultimately the nanotube film is formed) is not particularly limited and can include essentially any desired solid substrate. The substrate can be selected such that the nanotube film functionalizes the substrate or otherwise improves the properties of the substrate (i.e., the carbon nanotube material-containing film imparts its desired properties (e.g., electrical, mechanical, thermal) to the substrate / composite). Examples of substrates include, but are not limited to, all types of paper (e.g., magician's paper, highly nitrified paper, paper mulberry, carbon fiber paper, glass fiber paper), woven metal cloth, woven glass fiber cloth, common polymer surfaces such as polyester, polycarbonate, polyamide, acrylic, polyurethane, polymethylmethacrylate, cellulose, triacetyl cellulose, amorphous polyolefin, polylactic acid, polyhydroxyalkanoate, and polybutylene adipate co-terephthalate, and the like, woven polymer cloth, wood, silicon, glass, quartz, and common metal surfaces such as stainless steel, aluminum, iron, gold, metal foil, and silver.

[0072] Resulting articles may include, for example, epoxy and engineering plastic composites, filters, actuators, adhesive composites, elastomeric composites, materials for thermal management (interface materials, spacecraft radiators, avionics housings, and printed circuit board heat dissipation surfaces, materials for heat transfer applications such as coatings, etc.), aircraft, marine substructures and automotive structures, dimensionally stable structures for spacecraft and sensors, materials for ballistic applications such as air, marine, and land vehicle protective panels, bulletproof vests, protective vests, and protective helmets, tear and abrasion resistant materials for use in parachutes, such as reusable launch vehicle cryogenic fuel tanks and unlined pressure vessels, fuel lines, packaging for electronic, optoelectronic, or microelectromechanical components or subsystems, rapid prototyping materials, photovoltaic devices, energy storage devices such as batteries, capacitors, or supercapacitor fuel cells, medical materials, composite fibers, improved flywheels for energy storage, sporting goods and consumer goods, O-rings, gaskets, or seals.

[0073] For purposes of illustration, hereinafter, a slurry for secondary battery electrodes produced using the nanotube dispersion of the present disclosure, as well as secondary battery electrodes and secondary batteries produced using the slurry, are described.

[0074] The slurry for secondary battery electrodes of the present disclosure contains an electrode active material and the nanotube dispersion described above. That is, the slurry for secondary battery electrodes of the present disclosure contains at least an electrode active material, a carbon nanotube material, a polyether alkanolamine dispersant described above, and a dispersion medium. In one embodiment, the dispersion medium includes water alone or a mixture of water and the above solvent.

[0075] The electrode active material contained in the slurry for secondary battery electrodes of the present disclosure is a material that accepts and donates electrons in an electrode of a secondary battery. For example, when the secondary battery is a lithium ion secondary battery, the electrode active material is usually a material that can absorb and release lithium.

[0076] In one embodiment, the electrode active material is a positive electrode active material. Examples of the positive electrode active material include known positive electrode active materials, such as lithium-containing cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium-containing nickel oxide (LiNiO2), lithium-containing composite oxide of Co-Ni-Mn (Li(CoMnNi)O2), lithium-containing composite oxide of Ni-Mn-Al, lithium-containing composite oxide of Ni-Co-Al, olivine-type lithium iron phosphate (LiFePO4), olivine-type lithium manganese phosphate (LiMnPO4), Li2MnO3-LiNiO2 solid solution, Li 1+x Mn 2-x O4(0 <X<2)、Li[Ni 0.17 Li 0.2 Co 0.07 Mn 0.56 ]O2, and LiNi 0.5 Mn 1.5 Lithium-rich spinel compounds represented by the formula O4 are included, but are not limited to these. do not have.

[0077] According to another embodiment, the electrode active material is a negative electrode active material. Examples of the negative electrode active material include carbon-based negative electrode active materials, metal-based negative electrode active materials, and negative electrode active materials formed by combining these materials.

[0078] A carbon-based negative electrode active material can be defined as an active material that contains carbon as its main skeleton and that can have lithium inserted (i.e., "doped") into its main skeleton. Examples of carbon-based negative electrode active materials include carbonaceous materials and graphitic materials.

[0079] Examples of carbonaceous materials include graphitized carbon and non-graphitized carbon, a representative of which is glassy carbon having a structure similar to an amorphous structure. Graphitized carbon can be a carbon material made using tar pitch obtained from petroleum or coal as a raw material. Specific examples of graphitized carbon include coke, mesocarbon microbeads (MCMB), mesophase pitch-based carbon fiber, and pyrolytic vapor-grown carbon fiber. Examples of non-graphitized carbon include phenolic resin calcined product, polyacrylonitrile-based carbon fiber, quasi-isotropic carbon, furfuryl alcohol resin (PFA) calcined product, and hard carbon.

[0080] Examples of graphite materials include natural graphite and artificial graphite. Artificial graphite can be obtained by heat treating graphitized carbon-containing carbon mainly at 2800°C or higher, graphitized MCMB obtained by heat treating MCMB at 2000°C or higher, and graphitized mesophase pitch-based carbon fiber obtained by heat treating mesophase pitch-based carbon fiber at 2000°C or higher.

[0081] A metal-based negative electrode active material can be defined as an active material that contains a metal, whose structure usually contains an element that allows lithium insertion, and that exhibits a theoretical electric capacity of 500 mAh / g or more per unit mass when lithium is inserted. In the case of a metal-based negative electrode active material, for example, lithium metal, elemental metals that can be used to form lithium alloys (e.g., Ag, Al, Ba, Bi, Cu, Ga, Ge, In, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, etc.) and their alloys, as well as their oxides, sulfides, nitrides, silicides, carbides, and phosphides, can be used. Among these metal-based negative electrode active materials, silicon-containing active materials (silicon-based negative electrode active materials) may be suitable. Examples of silicon-based negative electrode active materials include silicon (Si), silicon-containing alloys, SiO, SiO x and composite materials of conductive carbon and Si-containing materials obtained by coating the Si-containing material with conductive carbon or combining them.

[0082] Other components that can be contained in the slurry for secondary battery electrodes include, but are not limited to, binders, conductive materials other than carbon nanotube materials, reinforcing materials, leveling agents, wetting agents, viscosity modifiers, crosslinking agents, antioxidants, electrolysis solution additives, and any mixtures thereof.

[0083] In one embodiment, the total solids concentration of the slurry for secondary battery electrodes is not particularly limited, so long as the slurry has a viscosity and flowability that allows coating and immersion to be performed. Typically, this can be from about 10% by weight to about 80% by weight.

[0084] The secondary battery electrode slurry can be prepared by mixing the nanotube dispersion with the electrode active material and other optional components. The mixing method and mixer used are not particularly limited, and can be, for example, the one used for preparing the nanotube dispersion. As for the mixing order, all the components can be added at once, or the components can be added in batches and then mixed together.

[0085] According to another embodiment, there is provided an electrode for a secondary battery comprising: a current collector; and a layer formed on the current collector, the layer being formed from the slurry for a secondary battery electrode described above. That is, the electrode mixed material layer includes at least an electrode active material and a carbon nanotube material. Note that the components contained in the electrode mixed material layer are the same as those contained in the slurry for a secondary battery electrode described above. The preferred ratio of these components is the same as that described above for the slurry for a secondary battery electrode.

[0086] The secondary battery electrode of the present disclosure is manufactured, for example, through a process of applying the secondary battery electrode slurry disclosed herein onto a current collector (the "application process"), and drying the secondary battery electrode slurry applied onto the current collector to form a layer on the current collector (the "drying process").

[0087] The method of coating the above-described slurry for secondary battery electrodes on the current collector is not particularly limited, and generally known methods can be used. Specific examples of coating methods that can be used include doctor blade method, dip coating method, reverse roll coating method, direct roll coating method, gravure coating method, extrusion coating method, and brush coating method. In the coating process, the slurry for secondary battery electrodes can be coated on only one side of the current collector, or it can be coated on both sides of the current collector. The thickness of the coating film of the slurry for secondary battery electrodes on the current collector after coating and before drying can be appropriately set according to the thickness of the electrode mixture material layer obtained after drying.

[0088] The current collector to which the secondary battery electrode slurry is applied is a material having electrical conductivity and electrochemical durability. Specifically, the current collector can be made of, for example, iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, or a carbon nanotube sheet. In one embodiment, the current collector is a carbon nanotube sheet containing carbon nanotubes characterized by having one or more of the following characteristics: (i) a diameter of about 1 to 100 nm, (ii) a length of about 0.1 to 10 mm, and (iii) a density of about 0.3 to 1.9 g / cm. 3 (iv) an aspect ratio of at least about 100,000; (v) a strain at break of about 1.8-7%; and (vi) a surface area of ​​about 100-300 m. 2 / g. It is possible to use one of the above materials individually, or two or more of them in combination in freely chosen ratios.

[0089] The slurry for the secondary battery electrode on the current collector can be dried by a commonly known method without any specific limitation. Examples of drying methods include: drying with warm, heat, or low humidity air (e.g., in a convection oven); drying in a vacuum; and drying by irradiation with infrared light, electron beam, etc. Drying the slurry for the secondary battery electrode on the current collector in this manner forms a layer on the current collector, thereby providing a secondary battery electrode comprising the current collector and the layer.

[0090] After the drying step, the electrode can be further subjected to a pressing step, such as mold pressing or roll pressing. The pressing process can improve the intimate adhesion between the electrode composite material layer and the current collector. In some embodiments, after the drying step, the electrode can be subjected to a temperature of at least 180° C. for a period of time to further improve its properties.

[0091] According to another embodiment, a secondary battery is provided. The secondary battery of the present disclosure includes a positive electrode, a negative electrode, an electrolyte, and a porous separator. In the secondary battery of the present disclosure, the electrode for a secondary battery of the present disclosure is used as at least one of the positive electrode and the negative electrode. The secondary battery of the present disclosure has a reduced battery resistance because it includes the electrode for a secondary battery of the present disclosure. At the same time, the life characteristics are improved.

[0092] The secondary battery of the present disclosure is preferably a secondary battery in which the electrode for a secondary battery of the present disclosure is used as a positive electrode. As an example, the secondary battery is described below as a lithium ion secondary battery, but the secondary battery of the present disclosure is not limited to the following example and may include a lithium sulfur secondary battery, a sodium ion secondary battery, or a lithium air secondary battery.

[0093] Known electrodes used in the manufacture of secondary batteries can be used in the secondary battery of the present disclosure as electrodes other than the electrodes for secondary batteries described above, without any particular specific restrictions. Specifically, an electrode obtained by forming an electrode mixed material layer on a current collector by a known manufacturing method can be used as an electrode other than the electrodes for secondary batteries described above.

[0094] The electrolyte is usually an organic electrolyte obtained by dissolving a supporting electrolyte in an organic solvent. The supporting electrolyte of the lithium ion secondary battery can be, for example, a lithium salt. Examples of lithium salts include LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, and (C2F5SO2)NLi. Of these, LiPF6, LiClO4, and CF3SO3Li are preferred because they are easily dissolved in a solvent and show a high degree of ionization, and LiPF6 is particularly preferred. One of these supporting electrolytes can be used individually, and two or more of these supporting electrolytes can be used in combination in a freely selected ratio. In general, lithium ion conductivity tends to increase when a supporting electrolyte with a high degree of ionization is used. Thus, lithium ion conductivity can be adjusted through the type of supporting electrolyte used.

[0095] The organic solvent used in the electrolyte is not particularly limited as long as the supporting electrolyte dissolves in it. Suitable examples include: carbonate esters, such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), and ethyl methyl carbonate (EMC); esters, such as γ-butyrolactone and methyl formate; ethers, such as 1,2-dimethoxyethane and tetrahydrofuran; and sulfur-containing compounds, such as sulfolane and dimethyl sulfoxide. Mixtures of these organic solvents can also be used. Among these solvents, carbonate esters are preferred due to their high dielectric constant and wide stable potential range, and a mixture of ethylene carbonate and ethyl methyl carbonate is more preferred.

[0096] The concentration of the supporting electrolyte in the electrolytic solution can be appropriately adjusted, and is, for example, preferably 0.5% by mass to 15% by mass, more preferably 2% by mass to 13% by mass, and even more preferably 5% by mass to 10% by mass. Known additives, such as fluoroethylene carbonate and ethyl methyl sulfone, can be added to the electrolytic solution.

[0097] The porous separator functions as both an electrical insulator and a mechanical support, sandwiched between the negative and positive electrodes to prevent physical contact between the two electrodes. In one embodiment, the porous separator is a polyolefin membrane. The polyolefin can be a homopolymer or a heteropolymer, and can be linear or branched. When a heteropolymer derived from two monomeric components is used, the polyolefin can be assumed to be in any copolymer chain configuration, including block or random copolymers. The same applies when the polyolefin is derived from more than two monomeric components. By way of example, the polyolefin membrane can be made of polyethylene (PE), polypropylene (PP), a blend of PE and PP, or a laminated porous film of PE and / or PP. be.

[0098] In other examples, the porous separator can be formed from another polymer selected from the following: polyethylene terephthalate, polyvinylidene fluoride, polyamide (nylon), polyurethane, polycarbonate, polyester, polyether ether ketone, polyether sulfone, polyimide, polyamide imide, polyether, polyoxymethylene (e.g., acetal), polybutylene terephthalate, polyethylene naphthenate, polybutene, acrylonitrile-butadiene styrene copolymer (ABS), polystyrene copolymer, Polymethylmethacrylate (PMMA), polyvinyl chloride (PVC), polysiloxane polymers (such as polydimethylsiloxane (PDMS)), polybenzimidazole (PBI), polybenzoxazole (PBO), polyphenylene, polyarylene ether ketone, polyperfluorocyclobutane, polytetrafluoroethylene, polyvinylidene fluoride copolymers and terpolymers, polyvinylidene chloride, polyvinyl fluoride, liquid crystal polymers, poly(p-hydroxybenzoic acid), polyaramid, polyphenylene oxide, and / or combinations thereof. In yet another example, the porous separator can be selected from a combination of polyolefins (such as PE and / or PP) and one or more of the polymers listed above.

[0099] The porous separator can contain a single layer or multi-layer laminate made by either a dry process or a wet process. For example, a single layer of polyolefin and / or other polymers mentioned above can constitute the porous separator entity. However, as another example, multiple separate layers of similar or dissimilar polyolefins and / or polymers can be assembled into a porous separator. In one example, a separate layer of one or more polymers can be coated onto a separate layer of polyolefin to form a porous separator. Furthermore, a polyolefin (and / or other polymer) layer, and any other optional polymer layers, can be included in the porous separator as fibrous layers, etc., to help provide the porous separator with suitable structural and porosity properties. Still other suitable porous separators include those having a ceramic layer attached to the porous separator and those including ceramic fillers in a polymer matrix (i.e., an organic-inorganic composite matrix).

[0100] The secondary battery of the present disclosure can be manufactured, for example, by stacking a positive electrode, a negative electrode and a separator therebetween, rolling or folding the resulting laminate as necessary according to the shape of the battery, disposing the laminate in a battery container, injecting an electrolyte into the battery container, and sealing the battery container. In order to prevent pressure rise inside the secondary battery and the occurrence of overcharging or overdischarging, an overcurrent prevention device, such as a fuse or PTC device, an expanded metal, or a lead plate, can be provided as necessary. The shape of the secondary battery can be a coin type, a button type, a sheet type, a cylinder type, a prism type, a flat type, or the like. EXAMPLES

[0101] Comparative Example 1: 0.75% CNT-PVDF aqueous cathode dispersion A 5% aqueous solution of CMC (Walocel® CRT 2000, supplied by Dupont) was prepared by mixing with water in a FlackTek twin-axis orbital mixer at 3500 rpm for five 5-minute cycles for a total of 25 minutes to give a clear CMC solution. The CMC solution was allowed to sit overnight and mixed again before use. 13.4 g of the CMC solution was combined with 15 g of an aqueous PVDF suspension (Kynar Latex 32, supplied by Arkema), 0.5 g of carbon nanotubes (CNTs) available from Nanocomp Technologies, Inc. (Merrimack, NH), and 63.57 g of cathode active material (NMC-532, supplied by Targray) and mixed in a Flacktek mixer at 1900 rpm for 5 minutes. Unless otherwise noted, ingredients were used as in each process. The mixture was mixed at ambient temperature (i.e., about 25°C) for 15 minutes at 70 micron and 35 micron gaps using a three-roll mill (Torrey Hills Technology). The resulting dispersion was diluted to 30% with water, mixed in a Flacktek mixer at 1900 rpm for 5 minutes, and a portion was cast onto a spaced, tabbed printed circuit ("PC") board to obtain linear 4-point probe resistivity measurements. The cast film was dried in an open-air oven at 80°C for 1 hour. The cast film was calculated to be 0.75% CNT (by dry weight), 4% PVDF, 1% CMC, and the remainder active material. For this film, the calculated bulk resistivity of the cast film (average of 4 measurements) was 0.810 ohm-cm with a standard deviation of 0.013 ohm-cm (see Figure 2).

[0102] Example 1: 0.75% CNT-CMC / PVDF aqueous cathode dispersion with polyetheralkanolamine dispersant. A 5% solution of CMC (Walocel® CRT 2000, supplied by Dupont) in water was prepared by mixing with water in a FlackTek twin-axis orbital mixer at 3500 rpm for five 5-minute cycles, totaling 25 minutes, to give a clear CMC solution. The CMC solution was allowed to sit overnight and mixed again before use. 13.4 g of the CMC solution was combined with 15 g of PVDF aqueous suspension (Kynar Latex 32, supplied by Arkema), 0.5 g of carbon nanotubes (CNTs) available from Nanocomp Technologies, Inc. (Merrimack, NH), 3 g of water containing 25% polyether alkanolamine dispersion (JEFFSPERSE® X-3202, available from Huntsman Petrochemical LLC, The Woodlands, TX), and 63 g of cathode active material (NMC-532, supplied by Targray) and mixed in a Flacktek mixer at 1900 rpm for 5 minutes. The resulting dispersion was processed 15 times using a three-roll mill (Torrey Hills Technology) with gaps of 70 microns and 35 microns. The resulting dispersion was diluted to 15% with water and mixed in a Flacktek mixer at 1900 rpm for 5 minutes, and a portion was cast on a PC board, fired, and tested as described above. For this film, the calculated bulk resistivity of the cast film (average of four measurements) was 0.410 ohm-cm with a standard deviation of 0.026 ohm-cm (see FIG. 2).

[0103] The bulk resistivities of the above two examples are shown in Figure 2. Example 1 has half the resistivity of the comparative example due to the presence of the polyetheralkanolamine dispersant. Surprisingly, it was found that the polyetheralkanolamine dispersant imparted a smooth texture to the aqueous dispersion that was well cast and free of macroaggregates of CNTs, while also imparting significantly lower resistivity.

[0104] While the making and using of various embodiments of the invention have been described in detail above, it will be appreciated that the invention provides numerous applicable inventive concepts that can be implemented in a wide variety of specific contexts. The specific embodiments discussed herein are merely illustrative of specific ways to make and use the invention and do not define the scope of the invention.

Claims

1. A dispersion medium; A polyether alkanolamine dispersant comprising a compound having the structure of the following formula (1) and a compound having the structure of the following formula (2): 【Chemistry 1】 【Chemistry 2】 In the formula, each R 1 is C 1 -C 100 is a hydrocarbyl group, and each R 2 is an alkoxylated hydrocarbyl group having the structure 【Chemistry 3】 In the formula, R 3 is C 1 -C 24 is a hydrocarbyl group, X 1 , X 2 , X 3 , X 4 , X 5 , and X 6 is independently selected from the group consisting of hydrogen, methyl, and ethyl at each occurrence, subject to the proviso that at least one of the two X groups attached to the same alkoxy unit is hydrogen; p, q, and r can each independently be an integer from 0 to about 100, subject to the proviso that at least one of p, q, and r is not 0; and each n is any integer from 1 to about 5; and carbon nanotube materials, A nanotube dispersion comprising:

2. The carbon nanotube material has (i) a diameter of about 1-100 nm, (ii) a length of about 0.01-10 mm, and (iii) a density of about 0.3-1.9 g / cm. 3 (iv) an aspect ratio of at least about 10,000; (v) a breaking strain of about 1.8-7%; and (vi) a surface area of ​​about 100-300 m. 2 10. The nanotube dispersion of claim 1, comprising carbon nanotubes characterized by one or more of the following characteristics:

3. The nanotube dispersion of claim 1 , wherein the dispersion medium is an aqueous dispersion medium.

4. The nanotube dispersion of claim 3 , wherein the aqueous dispersion medium comprises a substantial proportion of water.

5. 2. The nanotube dispersion according to claim 1, wherein the dispersion medium contains at least one of 3-methyl-2-oxazolidinone, 2-methyloxolane, dihydrolevoglucosanone, and N,N'-dimethylethyleneurea.

6. 10. The nanotube dispersion of claim 1, further comprising poly(vinylpyrrolidone), polyvinylpyridine, polystyrene, poly(4-vinylpyridine-co-styrene), poly(styrenesulfonate), lignosulfonic acid, lignosulfonate, poly(phenylacetylene), poly(meta-phenylenevinylene), polypyrrole, poly(p-phenylenebenzobisoxazole), anionic aliphatic surfactants, poly(vinyl)alcohol, polyoxyethylene surfactants, poly(vinylidene fluoride), carboxymethylcellulose, or mixtures thereof.

7. 2. The nanotube dispersion of claim 1, further comprising a conductive material selected from graphite, carbon black, carbon nanohorns, vapor-grown carbon fibers, milled carbon fibers obtained by pyrolysis of polymer fibers followed by pulverization, single-layer graphene, multi-layer graphene, carbon nonwoven sheets obtained through pyrolysis of polymer fiber nonwovens, and mixtures thereof.

8. The nanotube dispersion according to claim 1 , wherein the carbon nanotube material is dispersed in the dispersion medium.

9. An article comprising: a substrate; and a nanotube film formed on a surface of the substrate using the nanotube dispersion of claim 1.

10. The article of claim 9, wherein the nanotube film has a thickness ranging from about 0.02 μm to about 500 μm.

11. 10. The article of claim 9, wherein the substrate comprises paper, metal, foil, fiberglass, polymer, wood, silicon, glass, or quartz.

12. The article of claim 11 , wherein the substrate is paper or foil and the article is a current collector.

13. A slurry for a secondary battery electrode comprising an electrode active material, and a nanotube dispersion comprising an aqueous dispersion medium, a polyether alkanolamine dispersant, and a carbon nanotube material.

14. The slurry of claim 13 , wherein the electrode active material is a positive electrode active material.

15. The positive electrode active material may be lithium-containing cobalt oxide, lithium manganate, lithium-containing nickel oxide, lithium-containing composite oxide of Co-Ni-Mn, lithium-containing composite oxide of Ni-Mn-Al, lithium-containing composite oxide of Ni-Co-Al, olivine-type lithium iron phosphate, olivine-type lithium manganese phosphate, Li 2 MnO 3 -LiNiO 2 system solid solution, Li 1+x Mn 2-x O4 (0<X<2), Li[Ni 0.17 Li 0.2 Co 0.07 Mn 0.56 ]O 2 , or LiNi 0.5 Mn 1.5 O 4 15. The slurry of claim 14 comprising a lithium rich spinel compound represented by:

16. The slurry of claim 13 , wherein the electrode is a negative electrode active material.

17. 17. The slurry of claim 16, wherein the anode active material comprises a carbon-based anode active material, a metal-based anode active material, or a mixture of the carbon-based anode active material and the metal-based anode active material.

18. The slurry of claim 17 , wherein the metal-based negative electrode active material is a silicon-based negative electrode active material.

19. The slurry of claim 13 , wherein the carbon nanotube material is dispersed in the dispersion medium.

20. 13. An electrode comprising a current collector and a layer formed on the current collector using the slurry of claim 12.

21. A secondary battery comprising the electrode according to claim 20.

22. 22. The secondary battery of claim 21, wherein the secondary battery is a lithium ion battery, a lithium sulfur battery, a sodium ion battery, or a lithium air battery.